PIROLISIS MINYAK JARAK PAGAR MENGGUNAKAN KATALIS KARBON BERPORI - , Sri Warastuti; , Ir. Imam Prasetyo, M.Eng., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Biofuel development has gained the attention of researchers in recent years owing to reduction in conventional fossil fuel supplies and increased in environmental awareness. Jatropha oil is one of biofuel resources that is renewable, sustainable and environmentally friendly. In this study, jatropha oil was used to produce biofuel through pyrolysis process. This research is aimed to synthesis gasoline like fuel from jatropha oil over porous carbon catalyst. Catalytic pyrolysis of jatropha oil was carried out continuously in a fixed bed reactor made of quartz. Prior to pyrolysis process, nitrogen gas was flowed into the system for an hour. After the desired temperatures were achieved, jatropha oil was flowed through porous carbon catalyst. Pyrolysis was conducted at temperatures of 400, 450, 475 and 500 oC. Porous carbons used were carbon made of polymer of resorcinol phenol formaldehyde ethylene glycol (RPFEG) and resorcinol phenol formaldehyde (RPF), which had a dominant structure of mesoporous and microporous respectively. Volume of liquid product was recorded and sample of liquid product at different temperatures was analyzed with GC-MS to identify the components. The results showed that pyrolysis of jatropha oil over porous carbon produce a liquid product which has gasoline like fuel fraction where carbon with predominantly mesoporous produced a higher yield of biogasoline than the micropores. Pyrolysis of jatropha oil using predominantly mesoporous carbon catalyst gave the highest yield of biogasoline (69,51%) at a temperature of 450 oC, whereas under the same condition, kerosene and diesel like fuel fractions were present (9,71% and 5,03% respectively). The reaction kinetics was found to be 1,84 order with respect to liquid product where the activation energy and frequency factor were 41,9976 kJ/mol and 1,07 x 103 min-1 respectively.